2021
DOI: 10.3390/ijms222413326
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility of the CD57− NK Cells Expressing KIR2DL2/3 and NKG2C to iCasp9 Gene Retroviral Transduction and the Relationships with Proliferative Potential, Activation Degree, and Death Induction Response

Abstract: Nowadays, the use of genetically modified NK cells is a promising strategy for cancer immunotherapy. The additional insertion of genes capable of inducing cell suicide allows for the timely elimination of the modified NK cells. Different subsets of the heterogenic NK cell population may differ in proliferative potential, in susceptibility to genetic viral transduction, and to the subsequent induction of cell death. The CD57−NKG2C+ NK cells are of special interest as potential candidates for therapeutic usage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…CD57 − CD56 dim NKG2C + NK cells perform transitional stages in the process of NK cell differentiation and, at the same time, are characterized by a higher proliferative potential and survival. We have also revealed that CD57 − NK cells expressing NKG2C and KIR2DL2/3 are more susceptible to retroviral transduction compared to less differentiated NKG2C − KIR2DL2/3 − cells, which makes CD57 − NKG2C + KIR2DL2/3 + cells a promising source for genetic modification and further therapeutic application [ 47 ]. Therefore, approaches that facilitate the accumulation of CD57 − NKG2C + KIR2DL2/3 + cells are required for generating large numbers of NK cells without losing NKG2C and the inhibitory receptors KIR2DL2/3, which mark cytotoxic mature cells with an increased accumulation of cytotoxic vesicles [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD57 − CD56 dim NKG2C + NK cells perform transitional stages in the process of NK cell differentiation and, at the same time, are characterized by a higher proliferative potential and survival. We have also revealed that CD57 − NK cells expressing NKG2C and KIR2DL2/3 are more susceptible to retroviral transduction compared to less differentiated NKG2C − KIR2DL2/3 − cells, which makes CD57 − NKG2C + KIR2DL2/3 + cells a promising source for genetic modification and further therapeutic application [ 47 ]. Therefore, approaches that facilitate the accumulation of CD57 − NKG2C + KIR2DL2/3 + cells are required for generating large numbers of NK cells without losing NKG2C and the inhibitory receptors KIR2DL2/3, which mark cytotoxic mature cells with an increased accumulation of cytotoxic vesicles [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, NKG2C+ cells are a subset included in CD56dim CD16+ and CD56lo/-CD16+ NK cells initially identified as an expanded population in CMV infected individuals that is characterized by a primed state, including higher cytotoxic potential and enriched ADCC activity, and therefore, this subset has been considered to have memory-like properties (54,55). These cells originate from NKG2C-NKG2D+ precursors giving rise to immature NKG2C+ CD57-precursors and finally, mature NKG2C+ CD57+ memory cells (56)(57)(58)(59). In the case of HIV-1 infection, memory NKG2C+ NK cells have been shown to be capable of recognizing HLA-E expressing infected CD4+ T cells loaded with viral peptides (60,61).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the precursors of adaptive NK cells with the CD57 -CD56 dim NKG2C + phenotype retain many properties of adaptive cells, while being highly proliferative [7]. It has been previously shown that NK cells with the CD57 -CD56 dim KIR + NKG2C + phenotype are able to respond with intense expansion to stimulation by IL-2 and K562-mbIL21 feeder cells [9]. To evaluate the stability of KIR2DL2/3 expression in the adaptive NK cell progenitor subpopulation, heterogeneous CD57 -CD56 dim cultures of KIR2DL2/3-positive subsets were obtained.…”
mentioning
confidence: 99%